Mycoplasma genitalium and M. pneumoniae Regulate a Distinct Set of Protein-Coding Genes in Epithelial Cells - Ramos, Enrique I.; Das, Kishore; Harrison, Alana L.; Garcia, Anissa; Gadad, Shrikanth S.; Dhandayuthapani, Subramanian (Frontiers in Immunology, 2021)
Mycoplasma genitalium and M. pneumoniae are two significant mycoplasmas that infect the urogenital and respiratory tracts of humans. Despite distinct tissue tropisms, they both have similar pathogenic mechanisms and infect/invade epithelial cells in the respective regions and persist within these cells. However, the pathogenic mechanisms of these species in terms of bacterium-host interactions are poorly understood. To gain insights on this, we infected HeLa cells independently with M. genitalium and M. pneumoniae and assessed gene expression by whole transcriptome sequencing (RNA-seq) approach. The results revealed that HeLa cells respond to M. genitalium and M. pneumoniae differently by regulating various protein-coding genes. Though there is a significant overlap between the genes regulated by these species, many of the differentially expressed genes were specific to each species. KEGG pathway and signaling network analyses revealed that the genes specific to M. genitalium are more related to cellular processes. In contrast, the genes specific to M. pneumoniae infection are correlated with immune response and inflammation, possibly suggesting that M. pneumoniae has some inherent ability to modulate host immune pathways.